Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pntd.0001570
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Developing Mucosal Vaccine against Alveolar Echinococcosis (AE) Using Recombinant Tetraspanin 3: Vaccine Efficacy and Immunology

Abstract: Background We have previously evaluated the vaccine efficacies of seven tetraspanins of Echinococcus multilocularis (Em-TSP1–7) against alveolar echinococcosis (AE) by subcutaneous (s.c.) administration with Freund's adjuvant. Over 85% of liver cyst lesion number reductions (CLNR) were achieved by recombinant Em-TSP1 (rEm-TSP1) and -TSP3 (rEm-TSP3). However, to develop an efficient and safe human vaccine, the efficacy of TSP mucosal vaccines must be thoroughly evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 62 publications
0
39
0
1
Order By: Relevance
“…inhalation [29]–[31]. However, in our previous study it didn't induce satisfied intestinal IgA production [13]. Because the nature infection of AE is closely associated to gastrointestinal tract, intestinal IgA is thought to be the first lines of defences against early infection by E. multilocularis [32].…”
Section: Discussionmentioning
confidence: 93%
“…inhalation [29]–[31]. However, in our previous study it didn't induce satisfied intestinal IgA production [13]. Because the nature infection of AE is closely associated to gastrointestinal tract, intestinal IgA is thought to be the first lines of defences against early infection by E. multilocularis [32].…”
Section: Discussionmentioning
confidence: 93%
“…Targeting these parasite surface molecules have been used as a control strategy to reverse the host immunomodulation and allow the host immune system to recognize the parasite and eliminate them form the host [12]. Previous studies showed that TSP is expressed on the surface of helminthes [44,45]. Surface staining with anti-TSP LEL antibodies confirm that Bm TSP LEL is also expressed on the surface of B. malayi L3.…”
Section: Discussionmentioning
confidence: 99%
“…A proteomic analysis of the adult stage of E. granulosus in dogs was performed and a series of proteins associated with survival, development, movement and modulation were identified, and thus improved the repertoire of candidate proteins for vaccination, immunodiagnosis, and drug development [50]. Vaccine development against experimental rodent alveolar echinococcosis using a novel tetraspanin molecule was introduced in the symposium [51]. To overcome the difficulty in fox sampling, a new quantitative PCR to detect Echinococcus species in carnivore feces, which is useful for large-scale as well as fine spatial resolution studies, was presented [16].…”
Section: Reviewmentioning
confidence: 99%